2016
DOI: 10.1007/s10643-016-0821-y
|View full text |Cite
|
Sign up to set email alerts
|

Examining Services for Young Children with Autism Spectrum Disorder: Parent Satisfaction and Predictors of Service Utilization

Abstract: Autism spectrum disorder (ASD) is the fastest growing group of neurodevelopmental disorders in childhood. Earlier detection means an increased need for early intervention and other educational services. This study examined what services a sample of young children with ASD received, what variables predicted service utilization, and how satisfied parents were with the services. Sixty children (2–7 years) and their families from the Northwestern United States participated in the study. Results suggest that, on av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
27
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 26 publications
6
27
0
Order By: Relevance
“…The ages of detection, diagnosis and access to intervention reported by family members are markedly lower than those reported in some previous studies (Baio et al, 2018;Oswald, Haworth, Mackenzie, & Willis, 2017) but similar to those reported in others (Adelman & Kubiszyn, 2017;Daniels et al, 2017;McIntyre & Zemantic, 2017;Moh & Magiati, 2012). It is possible that the variation in families' reports of age at first access to services for children with ASD simply reflects differences in socio-economic status, since it has been observed that families with greater socio-economic resources enjoy better access to services and specialists.…”
Section: Discussionsupporting
confidence: 60%
“…The ages of detection, diagnosis and access to intervention reported by family members are markedly lower than those reported in some previous studies (Baio et al, 2018;Oswald, Haworth, Mackenzie, & Willis, 2017) but similar to those reported in others (Adelman & Kubiszyn, 2017;Daniels et al, 2017;McIntyre & Zemantic, 2017;Moh & Magiati, 2012). It is possible that the variation in families' reports of age at first access to services for children with ASD simply reflects differences in socio-economic status, since it has been observed that families with greater socio-economic resources enjoy better access to services and specialists.…”
Section: Discussionsupporting
confidence: 60%
“…A functional relationship between the P-ESDM via telehealth intervention and parent fidelity of intervention strategies was demonstrated. This result is consistent with literature that telehealth can be used as a mechanism to deliver naturalistic developmental behavioral interventions and achieve positive child outcomes (McIntyre & Zemantic, 2017;Wainer & Ingersoll, 2015). In rural areas, equity and access to early intervention and parent coaching services can be a challenge (Olsen, Fiechtl, & Rule, 2012).…”
Section: Telehealthsupporting
confidence: 89%
“…In this study, parent fidelity of implementation was shown to increase during the generalization and maintenance phases; a possible assurance that parents' sustained implementation may likely impact the child's developmental trajectory and targeted communication and social behaviors over time. This "real life" intensity of services is necessary for significant change in toddlers with ASD, and these results are congruent with other researchers who have demonstrated that parent involvement helps to facilitate generalization across environments (Brian et al, 2017;McIntyre & Zemantic, 2017;Wallace & Rogers, 2010).…”
Section: Increased Fidelity Of P-edsmsupporting
confidence: 85%
See 1 more Smart Citation
“…21 Children with ASD may use multiple services 17,19,22 ; however, little research has identified service use patterns and related characteristics among children with ASD. Rather, past research has been focused on specific services used (eg, psychotropic medication), [14][15][16][17][18][19]23,24 the number of services, 17 weekly service hours, 14,25,26 and/or certain combinations of services used (eg, behavioral intervention and schoolbased therapy). 22 Increased understanding of the services most likely to be used together and the characteristics associated with service use groups among children with ASD will provide a greater basis for studying health trajectories and help inform interventions that support shared decision-making about appropriate service use.…”
mentioning
confidence: 99%